Regional policy dialogue on warly warning early action mechanisms for the prevention of food crises - Rice, Brendan; Dimaranan, Betina (International Food Policy Research Institute, 2019)
A regional policy dialogue on early warning and early action mechanisms for the prevention of food crises was held in Accra, Ghana on 5 September 2019 to share challenges, lessons learned, and ways to improve these mechanisms. The event brought together more than 40 stakeholders from regional and international development agencies, government, civil society, and academia from Africa and abroad. Hosted by IFPRI through the Food Security Portal (FSP), the policy dialogue took place during the African Green Revolution Forum 2019 (AGRF). It was made possible by the European Union through its funding of the FSP.